Legal Protection of Trusmi Batik Copyright in the Perspective of National Cultural Protection - Rika Mustikawati; Anggita Dwi Kurniawati; Moh. Sulaiman; Harmono; Dadan Taufik Fathurohman (PT FORMOSA CENDEKIA GLOBAL, 2025)
Trusmi batik is a national cultural asset that requires legal protection. Therefore, local governments must participate in maintaining this cultural heritage so that it becomes the pride of the nation. This study discusses the legal protection of the copyright of Trusmi batik from the perspective of national cultural protection, with a focus on consumer protection. The objectives of the research are to find out how to implement the Copyright Law and the government's strategic steps, especially the government of Cirebon Regency, to protect the cultural heritage of batik in Trusmi Village. This study will use the empirical Judicial method, which uses a qualitative approach through interviews and case studies to analyze the application of copyright in the batik industry. The study's results show that even though the Laws and Regulations on Copyright have been implemented, there are still obstacles in law enforcement and understanding among craftsmen. On the other hand, consumers are often less aware of the importance of copyright, so they risk buying products that infringe copyright. This article suggests the need for socialization and education about copyright, as well as cooperation between the government, artisans, and consumers, to create a better ecosystem for copyright and consumer protection in the batik industry.